Deep inspiration breath-hold technique in left-sided breast cancer radiation therapy: evaluating cardiac contact distance as a predictor of cardiac exposure for patient selection - Rochet, Nathalie; Drake, Julie I.; Harrington, Kyla; Wolfgang, John A.; Napolitano, Brian; Sadek, Betro T.; Shenouda, Mina N.; Keruakous, Amany R.; Niemierko, Andrzej; Taghian, Alphonse G. (Practical Radiation Oncology, 2015)
The purpose of this study was to evaluate the efficacy of voluntary deep inspiration breath-hold (DIBH) over a free-breathing (FB) technique to minimize cardiac radiation exposure in radiation therapy of left-sided breast cancer. Also, to better select patients for DIBH, the correlation between cardiac contact distance (CCD) and cardiac dose was assessed.